The Implications of Dividend Policy, Debt Policy, and Institutional Ownership on the Firm Value of Banking Companies - Salsabila, Denaya Bethary; Setyahuni, Suhita Whini; Prawitasari, Dian; Kurniawan, Rudi (EAJ (Economic and Accounting Journal), 2025)
This study aims to evaluate the impact of dividend policy (DPR), debt policy (DER), and institutional ownership (KI) on firm value in 45 banking companies listed on the Indonesia Stock Exchange during the 2018–2023 period. Using a quantitative research method, panel data regression analysis was applied to identify the relationships between these variables. The research findings indicate that, overall, dividend policy, debt policy, and institutional ownership significantly influence firm value. This is demonstrated by an R-squared value of 0.760, meaning that 76% of the variation in firm value can be explained by these variables. More specifically, dividend policy (DPR) and institutional ownership (KI) have a significant positive effect on firm value, while debt policy (DER) also has a positive impact, though with slightly lower significance. These findings align with the signaling theory, which suggests that a stable dividend policy and high institutional ownership provide positive signals to investors regarding the company’s financial prospects and corporate governance quality. Additionally, from the perspective of agency theory, debt policy serves as a control mechanism that encourages management to use funds more efficiently, while institutional ownership strengthens oversight of managerial decision-making. Thus, this study provides valuable insights for investors and companies in formulating strategies to enhance shareholder value and market confidence.